Cembranoid Diterpenes from South China Sea Soft Coral Sarcophyton crassocaule - Hanyang Peng; Yanbo Zeng; Rui Zhang; Li Yang; Fei Wu; Cuijuan Gai; Jingzhe Yuan; Wenjun Chang; Haofu Dai; Xiachang Wang (Marine Drugs)
Cembranoid diterpenes are characteristic compounds of soft corals with diverse structures and significant activities, making them an important source of drug lead compounds. In this paper, five new cembranoid diterpenes, meijicrassolins A–E (1–5), were isolated from the soft coral Sarcophyton crassocaule, along with five previously reported compounds (6–10). The structures and absolute configuration for new compounds 1–5 were assigned by extensive spectroscopic analysis, single-crystal X-ray crystallography, quantum mechanical nuclear magnetic resonance (QM-NMR), and time-dependent density functional theory/electronic circular dichroism (TDDFT/ECD) calculations. Compounds 3, 4, and 9 showed moderate inhibition of nitric oxide generation in lipopolysaccharide (LPS)-stimulated RAW264.7 cells. Overall, our research results have enriched the library of secondary metabolites from soft corals, providing more molecular entities for subsequent research and development of related compounds.